PEMETAAN TAHAP BERPIKIR HOTS SISWA KELAS VIII SMP GIBS: SEBUAH ASESMEN DENGAN PENDEKATAN ANDERSON KRATHWOHL TAXONOMY - Azhari Wahyo Widodo; Istiqamah Istiqamah (Logat: Jurnal Bahasa Indonesia dan Pembelajaran, 2022)
Learning is an activity that involves cognition. In this XXI century, students are required to have various skills. One of them is critical thinking skills. PISA results in 2018 showed that there was a decrease compared to 2015. This indicates that action is needed to improve students' critical thinking skills. The first step that can be taken to improve critical thinking skills is to map students' thinking stages through Anderson Krathwohl Taxonomy (AKT). The purpose of this study is to describe the mapping of the HOTS thinking stage of VIII graders of SMP GIBS. This research uses mixed methods, quantitative and descriptive qualitative approaches. The data was obtained from the answers of 30 students of VIII graders of SMP GIBS. This research shows that the thinking ability of VIII graders of SMP GIBS is dominated by low-level thinking skills. On the dimension of conceptual knowledge, the number of students who have higher order thinking skills is only about 8 people or 26%. In procedural knowledge, the number of students who have higher order thinking skills is only about 7 people or 23%. In metacognitive knowledge, the number of students who have higher order thinking skills is only about 2 people or 6%.